Malignant Melanoma - Birdsell, D. S. (1974)
The diagnosis of malignant melanoma does not necessarily imply a grave prognosis. If the tumor is superficial, the chances of surgical cure may be good. Virtually all malignant melanoma arise from junctional nevi. Most nevi of the palms, soles, and genitalia are junctional nevi, therefore prophylactic excision of these nevi is recommended. The surgical treatment of malignant melanoma involves a wide excision and usually skin graft reconstruction. Chemotherapy and immunotherapy are used as adjuncts in the treatment of disseminated disease.